Simulation Education: Development Trends In Medicine - Abdurakhimova Lola Anvarovna (Zien Journals, 2021)
The article provides information about simulation education and its importance in medical education, development principles and the role of simulation training centers. At the same time, the stages of implementation of the simulation process in medical education in foreign countries, its specific aspects are covered. On the basis of didactic approaches, information is provided on the integration of the simulation process with the assessment system, its features and assessment indicators.
Keywords: simulation; trends; indicators; didactic approaches